This note facilitates you to prove good Trigonometry questions. So please use this note. I will try my best to post these types of notes from now.

\(\color{green}\text{Prove the following Identities :}\)

\((cosec A - sin A)(sec A - cos A)(tan A + cot A) = 1\) \(\boxed{\text{proved in 1 method}}\)

\(\frac{sec A - tan A}{sec A + tan A} = 1 - 2sec A \cdot tan A + 2tan^2A\)

\((sin A + cosec A)^2 + (cos A + sec A)^2 = 7 + tan^2A + cot^2A\) \(\boxed{\text{proved in 1 method}}\)

\(sec^2A \cdot cosec^2A = tan^2A + cot^2A + 2\)

\(\frac{1}{1 + cos A} + \frac{1}{1 - cos A} = 2cosec^2A\) \(\boxed{\text{proved in 1 method}}\)

\(\frac{sec A}{sec A + 1} + \frac{sec A}{sec A - 1} = 2 cosec^2A\)

\(\frac{1 + cos A}{1 - cos A} = \frac{tan^2A}{(sec A - 1)^2}\)

\(\frac{cot^2A}{(cosec A + 1)^2} = \frac{1 - sin A}{1 + sin A}\)

\(\frac{1 + sin A}{cos A} + \frac{cos A}{1 + sin A} = 2 sec A\)

\(\frac{1 - sin A}{1 + sin A} = (sec A - tan A)^2\)

If anybody proved any one of these I will mark that question as proved. But in Trigonometry one can prove a proof in many methods. So I will also mention in how many methods the proof is proved. Try your best to prove these. These are very easy if you apply little brain.

For more of these see my set Proof Based Notes

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewest5) \(\frac{1}{1 + cos A} + \frac{1}{1 - cos A}\)

\(\frac{1 - cos A + 1 + cos A}{1 - cos^2A}\)

\(\frac{2}{sin^2A} = 2 \cdot cosec^2A\)

Hence Proved

Log in to reply

1) \((cosec A - sin A)(sec A - cos A)(tan A + cot A) = 1\)

\(cosec A - sin A = \frac{1}{sin A} - sin A = \large\frac{1 - sin^2A}{sin A} = \frac{cos^2A}{sin A}\)

\(sec A - cos A = \frac{1}{cos A} - cos A = \large\frac{1 - cos^2A}{cos A} = \frac{sin^2A}{cos A}\)

\(tan A + cot A = \large\frac{sin A}{cos A} + \frac{cos A}{sin A} = \frac{sin^2A + cos^2A}{sin A \cdot cos A} = \frac{1}{sin A \cdot cos A}\)

\(LHS \implies \large\frac{cos^2A}{sin A} \times \frac{sin^2A}{cos A} \times \frac{1}{sin A \cdot cos A} = 1\)

\(\color{red}\text{Hence Proved}\)

Log in to reply

3) \((sin A + cosec A)^2 + (cos A + sec A)^2 = 7 + tan^2A + cot^2A\)

\(LHS \implies (sin A + cosec A)^2 + (cos A + sec A)^2 \)

\(\implies sin^2A + cosec^2A + 2 \cdot sin A \cdot cosec A + cos^2A + sec^2A + 2 \cdot cos A \cdot sec A\)

\(\implies sin^2A + cos^2A + 2 + cosec^2A + sec^2A + 2\) (since \(sin A \cdot cosec A = cos A \cdot sec A = 1\))

\(\implies 1 + 4 + 1 + tan^2A + 1 + cot^2A \) (since \(cosec^2A = 1 + cot^2A\) and \(sec^2A = 1 + tan^2A\))

\(\implies 7 + tan^2A + cot^2A\)

\(\color{green}\text{Hence Proved}\)

Log in to reply